2006
DOI: 10.1345/aph.1g715
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Chemical Stability of Pemetrexed in Infusion Solutions

Abstract: Pemetrexed is chemically stable for 2 days at room temperature and 31 days refrigerated in dextrose 5% injection and NaCl 0.9% injection. However, substantial numbers of microparticulates may form in pemetrexed diluted in the infusion solutions in PVC bags, especially during longer periods of refrigerated storage. Limiting the refrigerated storage period to the manufacturer-recommended 24 hours will limit particulate formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 2 publications
(1 reference statement)
2
16
0
Order By: Relevance
“…Therefore, pemetrexed was determined to be stable in extracted human matrix for up to 24 h at 15 • C. Previous stability studies of pemetrexed, performed in dextrose 5% injection and NaCl 0.9% infusion [20], demonstrated that pemetrexed is chemically stable for 1 day at 15 • C.…”
Section: Tablementioning
confidence: 99%
“…Therefore, pemetrexed was determined to be stable in extracted human matrix for up to 24 h at 15 • C. Previous stability studies of pemetrexed, performed in dextrose 5% injection and NaCl 0.9% infusion [20], demonstrated that pemetrexed is chemically stable for 1 day at 15 • C.…”
Section: Tablementioning
confidence: 99%
“…The chemical stability of pemetrexed solutions diluted in 0.9% sodium chloride (0.9% NaCl) and 5% dextrose (D5%) in PVC infusion bags at 2–8°C was determined by High Performance Liquid Chromatography (HPLC) for 1 month by Zhang and Trissel1 and Rondelot et al 2. However, subvisual examination shows an increase in turbidimetry and in the number of microparticulates after storage at 2–8°C.…”
Section: Introductionmentioning
confidence: 99%
“…However, subvisual examination shows an increase in turbidimetry and in the number of microparticulates after storage at 2–8°C. The hypothesis of an interaction with PVC was advanced and the use of an inline filter was advised 1. The discrepancy between the nephelometric evaluation and HPLC analysis could be due to the requirement to dilute the samples with the HPLC method.…”
Section: Introductionmentioning
confidence: 99%
“…Pemetrexed, in combination with cisplatin is also indicated for the treatment of patients with malignant pleural mesothelioma whose disease is unresectable or who are otherwise not candidates for curative surgery (Adjei et al, 2003). Pemetrexed disodium heptahydrate has the chemical name According to literature survey, few methods were reported about evaluation of assay of pemetrexed and its stability in solutions by HPLC (Saravanan et al, 2007), (Banu et al, 2010), (Rondelot et al, 2007), (Zhang et al, 2006). Few methods describe about LC-MS studies of pemetrexed and its metabolites in biological fluids like plasma and urine (Roland et al, 2010), (Meesters et al, 2010), (Li Wang et al, 2006) (Rivory et al, 2001).…”
Section: Introductionmentioning
confidence: 99%